Evaluasi Kinerja PDAM Kota Probolinggo dalam Perspektif Balanced Scorecard - Hubaisy, Zarrin; Suharsono, Agus; Helpiastuti, Selfi Budi (University of Jember)
Regional Water Company (PDAM) is one form of Local Authority-Owned Enterprise (BUMD) that provides services in the provision of clean water to the society. Although in the year 2010, it was in the “healthy” category, in some important ways it still has problems, such as financial target that was achieved only 60%, the clean water service coverage of downtown population which is imbalance with the number of population, water production value which is still higher than the water sale to the community members as well as the efficiency level of employees toward the water connection which has not reached the target. In order to improve the company services and development, it is necessary to measure the performance of the Regional Water Company (PDAM) of Probolinggo City. Balanced Scorecard Perspective was used in this research. Time series data were collected by the document study and was analyzed with descriptive statistical technique. The analysis results were presented in graphical form. The research was intended to evaluate the PDAM performance of Probolinggo City. The results showed that, in the balanced scorecard perspective, PDAM performance of Probolinggo City in 2009 – 2011 was categorized “not good”. Keywords: public organization, balanced scorecard